Crowd Scenes Movies and Mass Politics - Tratner, Michael (Fordham University Press, 2008)
The movies and the masses erupted on the world stage together. In a few decades around the turn of the twentieth century, millions of persons who rarely could afford a night at the theater and had never voted in an election became regular paying customers at movie palaces and proud members of new political parties. The question of how to represent these new masses fascinated and plagued politicians and filmmakers alike. Michael Tratner examines the representations of masses-the crowd scenes-in Hollywood films from The Birth of a Nation through such popular love stories as Gone with the Wind, The Sound of Music, and Dr. Zhivago. He then contrasts these with similar scenes in early Soviet and Nazi films. What emerges is a political debate being carried out in filmic style. In both sets of films, the crowd is represented as a seething cauldron of emotions.